Changes of the complement system and rheological indicators after therapy with rheohemapheresis. (May 2015) - Blaha, M.; Andrys, C.; Langrova, H.; Studnicka, J.; Drsata, J.; Lanska, M.; Blaha, V.; Zak, P.
Abstract: Introduction: In the last 10 years, many studies have been published on the role of the complement system in microcirculation disorders. However, as for the changes of complement components after rheohemapheresis, there is still a lack of detailed data in the literature. Complement changes may play an important role in pathogenesis of some microcirculation disorders, such as age-related macular degeneration and acute hearing loss. The objective of this study was to investigate the effect of rheohemapheresis on the basic complement pathways. Patients and methods: 32 patients were treated with rheohemapheresis, including 16 patients (10 men and 6 women) for age-related macular degeneration (AMD), mean age 69.7 ± 6.06 years (range 62–87 years) and 16 patients (11 men and 5 women) aged 56.4 ± 11.5 (range 34–73 years) for acute hearing loss. Results: Rheohemapheresis led to a significant drop of all three complement-activation pathways in both groups of patients. Moreover, complement factor H was also reduced. Conclusion: The observed reduction in all three basic complement activation pathways after rheohemapheresis could be clinically important. The search continues both to find substances which influence complement systems and to develop more effective new drugs that require less frequent administration and that provide improved intraocular therapy for AMD patients.